Study of Logo Teaching Methods in Design Colleges - Farid, Rudy; Astuti, Marisa; Supandi, Fajar Persada (Universitas Negeri Medan, 2025)
Design colleges play a key role in shaping competent future designers, especially in the context of logo designing, which is an important element in a brand or organization's identity. The teaching of logo designing in design colleges varies and faces challenges, so there is a need for in-depth research on its teaching methods. Teaching methods are strategies used to convey knowledge and skills to students, involving steps such as concept explanation, demonstration, practical exercises, feedback, iteration, and collaboration. The design teaching method is a specialized approach to design learning, focusing on developing aesthetic understanding, design concepts and technical skills. The design teaching process includes steps such as concept explanation, demonstration, practical exercises, feedback, iteration, and collaboration. This research aims to analyze logo design teaching methods in design colleges, evaluating their effectiveness in developing students' understanding, skills, creativity, and problem-solving. The research will also explore the potential utilization of technology in teaching logo design. The research results are expected to provide recommendations and guidelines for design colleges to improve the quality of logo design teaching, prepare students for the competitive design industry, and innovate teaching methods in an era of rapid design development.